The Improvement of Attitude Competence’s Students With Implementation of Learning Community Strategy Through Inquiry Learning Model On Structure and Fuction of Plant Tissue Material Class VIII in SMPN 12 Padang - Ivo Novidsa; Syamsurizal Syamsurizal; Rahmawati Darussyamsu (Bioeducation Journal, 2017)
The learning process will be more meaningful by doing together to form a community, it will be improve the achievement of the competence of students. Strategies that can create a learning process together is a Learning Community (LC) strategy. LC strategy can be applied through learning models, especially learning models that require joint discussion and problem solving. One such learning model is the inquiry learning model. The purpose of this study is to see the effect of the implementation of the LC strategy through the inquiry learning model to the achievement of the attitude competence of students. This research conducted at SMPN 12 padang class VIII about the structure and function of plant tissue materials. This research is a experimental research with Non-Randomized Control Group Post test Only Design. The population of this research is all students of class VIII SMPN 12 Padang. The sample in this research is all students of class VIII.2 and VIII.3 SMPN 12 Padang. Data of this research obtained by used observation method and analyzed by used statistic t-test. The result showed that eksperimental class and control class have different achievement of the attiude competence with t calculate is 3,98 and t table is 1,67 with α 0,05. It showed that t calculate > t table, so it concluded that LC strategy through inqury learning model can improved the achievement of the attitude competence of students.